Persistence and detection of black truffle ectomycorrhizas in plantations: comparison between two field detection methods (MYCORRHIZA, 2014)
Owners of black truffle (Tuber melanosporum) plantations are concerned about the persistence of its mycorrhizas and mycelium in the soil, especially until the appearance of the ``truffle burn{''} areas and the triggering of sporocarp production, at least 5-7 years after planting truffle-inoculated seedlings. During this period, the farmer does not know whether his management is promoting black truffle development. To study the presence and abundance of T. melanosporum ectomycorrhizas in plantations, two sampling methods, direct sampling of root tips and soil core collection, are compared by analyzing 48 evergreen oak trees (Quercus ilex) inoculated with truffle. Those trees are grouped by age (< 6, 6-9, > 9 years old) and presence or absence of truffle production. T. melanosporum was present in 46 out of the 48 studied trees, and its ectomycorrhizas appeared in 65 % of the ectomycorrhizal tips. Its abundance is significantly higher with productive trees and young trees. Direct sampling of root tips and soil core collection were equally effective in detecting this species, although soil core collection proved a better method to also evaluate ectomycorrhizal fungal diversity. To detect the presence of T. melanosporum in a given plantation, three samples suffice, with a single sample per random tree. Although the presence of mycorrhizas is not a sure sign of the future success of a black truffle plantation, its absence influences managers as to whether to continue culturing truffles in a plantation.

Ectomycorrhizal status of a mature productive black truffle plantation - Agueda, Beatriz; Fernández-Toirán, Luz Marina; de Miguel, Ana María; Martínez Peña, Fernando (Forest Systems; Vol 19, No 1 (2010), 2010)
The truffle-plantation “Los Quejigares” was planted in 1971 by AROTZ-CATESA company. It is a 600 ha plot of Quercus ilex mycorrhizated with Tuber melanosporum at 1250 m a.s.l. on calcareous soil. This plantation is the largest of the world and one of the eldest truffle-plantations of Spain and it is in full production. Knowledge of the mycorrhizal status of a mature black truffle plantation is significant for the improvement of truffle cultivation. Ectomycorrhizae were studied for knowing T. melanosporum persistence and diversity and abundance of other ectomycorrhizal types. Roots of 16 holmoaks were sampled, 12 trees produce truffle sporocarps and four did not. It was found a mean of about 70% of T. melanosporum ectomycorrhizae in all the studied trees, independently of their capacity to produce or not sporocarps. Also, 105 more different ectomycorrhizal types were found. In spite of the high number of morphotypes found, it seems that they do not replace T. melanosporum, showing that there is a coexistence between species in the fungal community associated to the roots.
Keywords: AROTZ-CATESA company; characterization of ectomycorrhizae; fungal diversity; Quercus ilex; truffle plantations; Tuber melanosporum